Will Facebook save or destroy social capital? An empirical investigation into the effect of online interactions on trust and networks - Fabio Sabatini; Francesco Sarracino (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Studies in the social capital literature have documented two stylised facts: first, a decline in measures of social participation has occurred in many OECD countries. Second, and more recently, the success of social networking sites (SNSs) has resulted in a steep rise in online social participation. Our study adds to this body of research by conducting the first empirical assessment of how online networking affects two economically relevant aspects of social capital, i.e. trust and sociability. We find that participation in SNSs such as Facebook and Twitter has a positive effect on face to face interactions. However, social trust decreases with online interactions. Several interpretations of these findings are discussed.
Additional information: We gratefully acknowledge the support of the Laboratory for Comparative Social Research at the National Research University Higher School of Economics. We are indebted to Ronald F. Inglehart, Eduard Ponarin, Luca Stanca, Christopher Swader, and Christian Welzel for useful comments and suggestions. We are grateful to Angelo Antoci, Alessandra Gualtieri, Malgorzata Micucka, and Mauro Sodini for precious conversations on our research topics. The paper also benefited from comments by Anna Amalkaeva, Luciano Canova, Barbara Collevecchio, Lucia Ferrone, Anna Nemirovskaya, Serban Tanasa, Balazs Telegdy and Bogdan Voicu, by participants at the 3rd LCSR International Workshop (Saint Petersburg, April 26-30, 2013), and at the Conference “Cultural and Economic changes under cross-national perspective” (Moscow, November 12-16, 2013). Usual caveats apply. The paper has been accepted for presentation at the XVIII ISA World Congress of Sociology (session on Sociology of Communication, Knowledge and Culture) to be held in Yokohama, Japan, on July 13-19, 2014.
Keywords: C36; D85; O33; Z13; 330; social participation; online networks; Facebook; Twitter; social capital; broadband; digital divide; Internet-mediated communication